A Role for LKP2 in the Circadian Clock of Arabidopsis - Schultz, Thomas F. (American Society of Plant Biologists, 2001)
A third member of the ZTL gene family was identified in the Arabidopsis genome and was named LKP2 (for LOV kelch protein2). A cDNA was isolated corresponding to this gene, and plants overexpressing LKP2 were generated. The overexpression of LKP2 resulted in arrhythmic phenotypes for a number of circadian clock outputs in both constant light and constant darkness, long hypocotyls under multiple fluences of both red and blue light, and a loss of photoperiodic control of flowering time. The LKP2 mRNA is not regulated by the circadian clock and was detected in all tissues examined. These results suggest that LKP2 functions either within or very close to the circadian oscillator in Arabidopsis. A model is presented for its mode of action.